2020
DOI: 10.1371/journal.pone.0226486
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of resting brain metabolism in treatment-resistant depression before and after treatment with olanzapine-fluoxetine combination

Abstract: Treatment-resistant depression (TRD) occurs in many patients and causes high morbidity and mortality. Because TRD subjects are particularly difficult to study especially longitudinally, biological data remain very limited. In a preliminary study to judge feasibility and power, 25 TRD patients were referred from specialty psychiatric practices. All were severely and chronically depressed and mostly had comorbid psychiatric disorders as is typical in TRD. Nine patients were able to complete all required componen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…The CUMS protocol is an established translationally relevant model for inducing behavioral symptoms commonly associated with clinical depression in rodents, such as anhedonia, altered grooming behavior and learned helplessness [ 22 ]. We created a chronic unpredictable mild stressful environment using stress and diet to induce antidepressant resistance.…”
Section: Methodsmentioning
confidence: 99%
“…The CUMS protocol is an established translationally relevant model for inducing behavioral symptoms commonly associated with clinical depression in rodents, such as anhedonia, altered grooming behavior and learned helplessness [ 22 ]. We created a chronic unpredictable mild stressful environment using stress and diet to induce antidepressant resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Also, when depressed patients on SSRI medications start to feel better, there is often an increase in the number of specific receptors, called 5-HT 2A , in the frontal cortex of the brain ( 65 , 66 ). Furthermore, one [ 18 F]FDG PET study showed olanzapine (an atypical antipsychotic) and fluoxetine (an SSRI) combination therapy yielded metabolic changes in the brain in patients with therapy-resistant depression, resembling those observed in individuals with therapy-responsive major depression ( 67 ).…”
Section: The Utility Of Pet In the Treatment Of Depressionmentioning
confidence: 99%
“…Another recent FDA-approved drug for treating TRD is Symbyax, which combines olanzapine (an atypical antipsychotic) and fluoxetine (a selective serotonin reuptake inhibitor) [116,117]. A recent study of 25 patients treated with Symbyax for 8 weeks showed a decline in amygdala activity and right ventromedial prefrontal metabolism, and these events were correlated with improvement in depression after the intervention [118].…”
Section: Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%